From Bench to Bedside and Back – Report on the European Helicobacter pylori Study Group Xth International Workshop on Gastroduodenal Pathology and Helicobacter pylori. (1st September 1998) - Thomson, ABR; Chiba, N; Sinclair, P
Abstract : The Xth International Workshop on Gastroduodenal Pathology and Helicobacter pylori was held in Lisbon, Portugal, from September 12 to 14, 1997. State-of-the-art reviews and research findings were presented to over 2000 participants. This review focuses on important new developments and serves as a rapid communication of clinically relevant material.